Estudo de nanofios monoatômicos por métodos de primeiros princípios - Frederico Ramos Fioravante (2002)
In the present work, results of electronic-structure calculations of metallic monoatomic nanowires with linear and zigzag planar geometry are presented. The calculations were performed using a first principles methodology based on the density functional theory within the generalized-gradient and the pseudopotential approximations. Calculations were performed for the following metals: ruthenium, rhodium, palladium, and silver from the 4d series, and iridium, platinum, and gold from the 5d series. Only one energy minimum was found for a zigzag shaped wire for each metal from the 4d series. This minimum at angles close to 600 in the zigzag vertices, resulting in a structure with coordination number equals to four. In the 5d series, two stable zigzag structures were found. One, with angles close to 600, and the other with angles close to 1200. We observe that the bond lengths grow with the atomic number Z. In every metal studied, the energy minimum of the zigzag wire close to 600 was more stable then the linear one. In the 5d series metals, the energy minimum of the zigzag wire close to 1200 was less stable than the energy minimum close to 600 and more stable than the linear one. Experimental results have showed the formation of monoatomic finite chains for 5d series metals, which are more difficult of being observed for the 4d metals. Our results agree with these observations, to the extent that a stable structure with coordination 2 is found for the 5d series metals and not for the 4d series metals.